2020
DOI: 10.2174/1381612826666200212121710
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Bacterial Biofilm Formation by Phytotherapeutics with Focus on Overcoming Antimicrobial Resistance

Abstract: : Bacteria within biofilms are more resistant to antibiotics and chemical agents than planktonic bacteria in suspension. Treatment of biofilm-associated infections inevitably involves high dosages and prolonged courses of antimicrobial agents; therefore, there is a potential risk of the development of antimicrobial resistance (AMR). Due to the high prevalence of AMR and its association with biofilm formation, investigation of more effective anti-biofilm agents is required. : From ancient times, herbs and spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…However, eighty percent of bacterial infections are related to the formation of bacterial biofilm, traditional antibacterial drugs could not permeate into the bacterial biofilm. Compared with planktonic bacteria, bacterial biofilm is 10–1000 times more resistant to antibiotics, which is the main cause of current bacterial drug resistance 32 . Metabolic regulation between distant bacteria in biofilms may involve electrochemical communication 33 .…”
Section: Discussionmentioning
confidence: 99%
“…However, eighty percent of bacterial infections are related to the formation of bacterial biofilm, traditional antibacterial drugs could not permeate into the bacterial biofilm. Compared with planktonic bacteria, bacterial biofilm is 10–1000 times more resistant to antibiotics, which is the main cause of current bacterial drug resistance 32 . Metabolic regulation between distant bacteria in biofilms may involve electrochemical communication 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Azithromycin used in our patient failed to eradicate C. coli in the blood. Inhibition of bacterial biofilm formation may be helpful for overcoming antimicrobial resistance and eliminating C. coli in the body [ 17 ]. Carbapenem is recommended for empirical treatment of Campylobacter bacteremia, however, C. coli has been shown elevated minimum inhibitory concentrations to meropenem in a patient with XLA due to overuse [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SEM results revealed that bacterial bio lm formation can be delayed after exposing the PA to the eucalyptus volatile oil. Bio lm formation is closely related to bacterial resistance (17)(18)(19)(20). Hence, destroying drug resistance is one of the mechanisms of the eucalyptus volatile oil that can be used in clinical bacterial treatment.…”
Section: Discussionmentioning
confidence: 99%